Evaluation of the Implementation of Occupational Health and Safety Management System at Lima Puluh Public Health Center, Batu Bara Regency, in 2025 - Purba, Lisdauli; Rambey, Harris; Ika Nur Saputri (JURNAL KESMAS DAN GIZI (JKG), 2025)
The Occupational Health and Safety Management System (OHSMS) is a critical component in ensuring a safe and healthy work environment, especially in healthcare service facilities such as community health centers (Puskesmas). This study aims to evaluate the implementation of OHSMS at Lima Puluh Public Health Center in Batu Bara Regency, focusing on three key components: policy establishment, planning, and implementation of OHS plans. A qualitative method with a case study approach was used, and data were collected through in-depth interviews, focus group discussions, observations, and documentation involving 10 informants from the District Health Office and the Puskesmas staff. The results show that although OHS policies have been formally established through official decrees, their implementation remains weak. Most team members were unaware of the decree, had not received OHS training, and lacked written work plans. Risk identification was informal and undocumented, and there was no systematic OHS planning document. The implementation of OHS activities was reactive and relied heavily on staff habits or personal initiatives. Out of 11 OHS standards for healthcare facilities, six had not yet been implemented, including hazard identification and risk control, application of ergonomic principles, periodic health examinations, immunization, management of facilities and infrastructure from an OHS perspective, and emergency or disaster preparedness. The study recommends strengthening management commitment, improving human resource capacity through training, and allocating specific budgets for OHS programs to optimize OHSMS implementation. The Batu Bara District Health and Family Planning Office, as the supervisor of OHSMS implementation, is expected to conduct continuous monitoring and evaluation to ensure sustainable improvement in OHS performance.